L’art du ballet de cour, ou performer le pouvoir dans l’espace germanique au XVIIe siècle - Marie-Thérèse Mourey (Etudes Epistémè)
The court ballet as an artistic genre was created in France at the end of the sixteenth century. While French productions have been much studied, this kind of performance was also cultivated in many princely courts across Germany until the beginning of the eighteenth century. Characterised by a massive, almost exclusive participation of the ruling princes and courtiers, the genre was not mere entertainment but a major tool for political communication, through the production of a symbolic image of the sovereign which reinforced his absolute political power – as is well known for Louis XIV and his celebration as Sun King and Apollo. This paper presents the lesser known German context: the practice of court ballet in the Empire confirms the reality of widespread cultural transfers within Europe. A survey and brief analysis of some specific ballets will uncover the structures and implications of the aesthetic system underlying the performance of power, especially the key role that was given to such symbolical forms as allegories or emblems, which were doomed to disappear in the eighteenth century.